Analisis Sentimen terhadap Gerai Minuman Xing Fu Tang Indonesia menggunakan Data Ulasan Google - Arifah Jihan Fadhillah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to obtain sentiment analysis results from Xing Fu Tang beverage outlets in Indonesia. The data used in this study comes from customer-written reviews of all Xing Fu Tang outlets in Indonesia on the Google Review site. Xing Fu Tang outlets are scattered across various cities, including Jakarta, Tangerang, Bekasi, Bandung, and Surabaya. The amount of data taken manually on June 4, 2020 is 500 reviews. The study uses the Naïve Bayes Multinomial classification method through the application of the Scikit-learn module. The overall precision of the sentiment analysis model developed during the study was 78%. Result of this study is only reliable during the time of study because amount of review will be updated and the customer opinions will change over time.